Skill‐up study of systemic endoscopic examination technique using narrow band imaging of the head and neck region of patients with esophageal squamous cell carcinoma: Prospective multicenter study. Issue 6 (20th June 2019) - Okamoto, Naoki; Morimoto, Hiroyuki; Yamamoto, Yoichi; Kanda, Keisuke; Nankinzan, Rino; Kasamatsu, Shingo; Yoshimura, Shigenobu; Kan, Motoyasu; Nakano, Akira; Hosaka, Shosuke; Watanabe, Yuuka; Arahata, Kyoko; et al.
Abstract : Objective: To evaluate the usefulness of a training program on endoscopic head and neck surveillance for beginner endoscopists. Methods: This prospective multicenter study included 13 beginner endoscopists from 10 institutions who received training in systematic observation techniques and diagnostic criteria, and the training involved hands‐on learning. Between May 2016 and February 2017, enrolled patients with current or previously diagnosed esophageal squamous cell carcinomas underwent head and neck surveillance using narrow band imaging (NBI) endoscopy, and histologically confirmed head and neck squamous cell carcinoma (HNSCC) detection rates, endoscopic image quality, and examination times were compared before (group A) and after (group B) the training program. Maximum possible score for the endoscopic images was 30 points. Results: A total of 330 patients, comprising 181 in group A and 149 in group B, were enrolled. Three patients with HNSCC were detected in group A (1.7%) and in group B (2.0%; P  = 1.000). Mean ± standard deviation (SD) examination times were 157 ± 71 s and 174 ± 109 s in groups A and B, respectively, ( P  =   0.073). Mean ± SD scores of the endoscopic images were 25.04 ± 5.47 points and 27.01 ± 4.35 points in groups A and B, respectively, ( P  <   0.001). Conclusion: The HNSCC detection rate based on the use of NBI on patients with ESCC did not improve after the training program for beginner endoscopists; however, endoscopic image quality improved significantly after the training program.